Perceived temporal distortions may explain the effect of precarity on intertemporal choices - Mitra, Arjun; Srivastava, Nisheeth (Frontiers in Psychology, 2025)
Existing research on how environmental volatility affect preferences suggests that preference for delayed rewards reduces in the presence of adverse shocks. Researchers typically use reward discounting frameworks to explain these shifts in temporal preferences as shifts in discount rates. In this manuscript, we reinterpret these preference shifts as changes in perceived time duration. Using data from multiple studies, we found that decreases in choice probability for delayed rewards correspond to increases in perceived delay duration, while keeping discount rates constant. Our empirical study also showed that individuals who experienced extension of perceived time during volatility preferred short-term plans more. Based on these findings, we suggest the necessity of considering perceived temporal distortions to understand preference shifts when one encounters environmental volatility.